Byzantium Al Ghassasina Political relation in The sixth century. (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This article Talks about relations between Byzantium and Al Ghassasina since Al Gassasina arrived in North west peninsula ( Belad Al Sham ) levant From The southern Arabian Peninsula As This article shows how could military and Political strength Proof AlGassasina Since sixth century transitional Through movement against The Byzantine Force in The region in 500 and it did not take long before AlGhassasina Approuched From Byzantium it robbed Salih Tribe allies Byzantium Their Standing they allied with Byzantium, They became loyal worker, especially in they Forties of the sixth century So they Frought beside Them against The Persians and their workers The kingdom of Al- Hira as aresult Pussling rippling in Flounce of AlGassacina On The Arabian Peninsula With The North West Parts Of The Northen Red sea. As The article Focuses on The devebpment Of relations between Byzantium and Al-Ghassasina turned To runner at The end Of The sixth Century making Byzantium Al-Ghassasing baser Political role ends and captivate Their king and Them exile and ran The remaining Princes.